Pelatihan Sistem Rantai Pasok dan Logistik untuk Meningkatkan Efisiensi Distribusi Produk Berbahan Dasar Kelor di PT. Mond Nature Lestari - Syifa Tanjung, Lailatul; Rusnedy, Hidayati; Kasini; Kumala Sari, Resy; Yusmita, Yesi (Faculty of Engineering University of Pahlawan Tuanku Tambusai, 2024)
This supply chain and logistics system training was held to increase the efficiency of distribution of Moringa-based products at PT. Mond Nature Lestari, a company engaged in the production and distribution of Moringa products which are known to have many health benefits. Even though this product has broad market potential, the company faces challenges in optimizing its distribution, especially related to high logistics costs and inefficiencies in supply chain management. This training program aims to provide understanding and skills to employees and company management in managing supply chains and logistics more efficiently, through material on supply chain analysis, inventory management, demand planning, as well as the application of information technology and digital-based logistics management systems. This training also includes an introduction to efficient transportation methods, optimal warehouse management, and the use of technology and logistics management software to reduce distribution costs. It is hoped that after the training, companies can reduce operational costs, speed up product distribution, and increase competitiveness by ensuring the even availability of Moringa products on the market. The success of this service will be seen from increased distribution efficiency, reduced logistics costs, and higher customer satisfaction.